Synthesis of Highly Functionalized Benzofuran-2-carboxamides by Ugi Four-Component Reaction and Microwave-Assisted Rap–Stoermer Reaction - Han, Weiwei; Wu, Jinlong; Dai, Wei-Min (Synlett, 2014)
A two-step, diversity-oriented synthesis of highly functionalized benzofuran-2-carboxamides has been developed. The Ugi four-component reaction of aromatic amines, isocyanides, 2-bromobenzaldehyde, and 2-bromoacetic acid was used to provide a collection of N-aryl 2-bromoacetamides. The latter were then reacted with selected salicyladehydes in the presence of Cs2CO3 in acetonitrile under controlled microwave heating at 90–140 °C for 15–40 minutes to furnish the benzofuran-2-carboxamides in moderate to good yields.
Keywords: amides; heterocycles; microwave; multicomponent reaction; phenols